Security challenges and guideline proposals for the development of underwater security - Prodan, Tonći; Kasum, Josip; Stošić, Marin, admiral; Ugrin, Ćiro (2020)
Maritime affairs are of great importance to the world economy, which is why the security of this area is of the utmost importance. Maritime security can be disrupted in a number of ways, and in this paper the greatest emphasis is placed on underwater security. Although states are making efforts to safeguard maritime and underwater security, there is still plenty of room to raise underwater security to a much higher level.
Bibliografija: 14 jed.
Abstract.
Keywords: Pomorstvo -- Sigurnost -- Podvodna sigurnost -- Kritična infrastruktura